PROGRAM KESELAMATAN DAN KESEHATAN KERJA, KOMPETENSI DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN DEPARTEMEN HUMAN RESOURCES OPERATIONAL PADA PT. GAJAH TUNGGAL TBK - Abdulloh Abdulloh; Asep Suwarna (JMB : Jurnal Manajemen dan Bisnis, 2020)
This is study aims to determine the effect of occupational safety and health, work competence and organizational commitment partially or simultaneously on the employee performance of the Human Resource Operations department at PT Gajah Tunggal, TBk. This study uses a descriptive quantitative research approach that relates to the numbers in the description describing in detail. For the sampling method in this is study the sampling method is used, namely saturated samples. The study sample was 55 respondents from employees of the operational human resources department at PT Gajah Tunggal, Tbk. so that the engineering approach with sampling used is saturated sample is expected to have a very small error gradation by being a population as a sample of 55 respondents. In this research. Analysis of the data used by researchers is with the help of calculating the SPSS 24 application to calculate the effect partially or simultaneously. Based on the results of simple regression and multiple regression in the SPSS 24 application. The results of the research can be partially proven that the occupational safety and health variables (X1) have a positive and significant effect on performance (Y) of 0.230 or 23%. The variable work competence (X2) has a positive and significant effect on performance (Y) of 0.503 or 50.3%. Organizational commitment variable (X3) has a positive and significant effect on performance (Y) of 0.434 or 43.4%. Simultaneously the occupational safety and health variables (X1), work competence (X2) and organizational commitment (X3) have a positive and significant effect on performance (Y) of 45.8%.Keywords: Occupational Safety And Health, Work Competence, Organizational Commitment, And Employee Performance